Invited Paper: A 1.8‐Gbps Intra‐Panel Interface with Power Reduction and EMI Suppression Schemes for Tablet PC Applications. Issue 1 (June 2014) - Lee, Kil‐Hoon; Lee, Dongmyung; Lim, Jung‐Pil; Tak, Wonho; Pae, Hansu; Lee, Jae‐Youl; Choi, Yoon‐Kyung; Hwang, Gyoocheol
Abstract An enhanced reduced voltage differential signaling (eRVDS) intra‐panel interface addressing both low‐power and low‐EMI requirements for tablet PC applications is presented. The proposed interface features a novel function called scrambled transition‐minimized coding (STMC) to perform both data pattern randomization and toggle reduction. Additionally, automatic skew calibration (ASC) is proposed to further reduce dynamic power and EMI radiation in the eRVDS interface. For verification, a WQXGA (2560times1600) TFT‐LCD system is implemented with the timing controller and source driver ICs that are fabricated using 65‐nm and 180‐nm CMOS processes, respectively. At the maximum operation speed of 1.8‐Gbps, the display module adopting the eRVDS interface demonstrated 24.3% power saving and 6.2‐dB suppression in EMI level.